Sistem Pakar Diagnosis Penyakit Pada Ayam Petelur Menggunakan Metode Certainty Factor - Rohmat Solikin; jusak jusak; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Chicken diseases often fear chicken farmers. In many cases, chicken diseases can reduce egg productivity of chickens. If there is one chicken affected and it doesn’t handle quickly and precisely, it indirectly can cause the other chickens affected as well that could potentially lead to death. On the other hand, there are limitation number of chicken veterinary in rural areas. Hence, the affected chickens cannot be handled as soon as possible. In this paper, we build an expert system with certainty factor method that is able to diagnose the chicken diseases computationally. Testing results shows that the expert system can identify chicken diseases with accuracy of 92,8%. The results were obtained by testing through 14 chickens that bear chicken diseases. Keywords: Expert System, Certainty Factor, Disease chicken